Microservices in Big Data Analytics : Second International, ICETCE 2019, Rajasthan, India, February 1st-2nd 2019, Revised Selected Papers /: Second International, ICETCE 2019, Rajasthan, India, February 1st-2nd 2019, Revised Selected Papers. (2019) - Unknown
No abstract available